2018
DOI: 10.1016/j.neuroimage.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the origins of EEG motion artefacts during simultaneous fMRI acquisition: Implications for motion artefact correction

Abstract: Motion artefacts (MAs) are induced within EEG data collected simultaneously with fMRI when the subject's head rotates relative to the magnetic field. The effects of these artefacts have generally been ameliorated by removing periods of data during which large artefact voltages appear in the EEG traces. However, even when combined with other standard post-processing methods, this strategy does not remove smaller MAs which can dominate the neuronal signals of interest. A number of methods are therefore being dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These EEG data were combined with neuronal EEG data acquired on a human subject outside of the MRI environment. The MAs were then corrected using motion information collected from each of the different methods in conjunction with number of previously described analysis pipelines Masterton et al, 2007;Maziero et al, 2016;Spencer et al, 2018). We showed that the MA was best corrected using the RLAS motion information combined with a multichannel recursive least squares (M-RLS) fitting algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These EEG data were combined with neuronal EEG data acquired on a human subject outside of the MRI environment. The MAs were then corrected using motion information collected from each of the different methods in conjunction with number of previously described analysis pipelines Masterton et al, 2007;Maziero et al, 2016;Spencer et al, 2018). We showed that the MA was best corrected using the RLAS motion information combined with a multichannel recursive least squares (M-RLS) fitting algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known discrepancy between the MAs induced on the scalp and reference layers (Spencer, Smith, Chowdhury, Bowtell, & Mullinger, 2018), a simple linear fit of each reference electrode signal to the corresponding scalp electrode signal was also performed. Given the known discrepancy between the MAs induced on the scalp and reference layers (Spencer, Smith, Chowdhury, Bowtell, & Mullinger, 2018), a simple linear fit of each reference electrode signal to the corresponding scalp electrode signal was also performed.…”
Section: Rlasmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple head motions such as nodding and shaking greatly affect the low frequency spectrum (less than 10 Hz) [18] of the EEG signals. A number of techniques have been proposed for motion correction [19]- [21], but none offer perfect correction of motion related artifacts [22]. Considering the difficulties associated with the correction of motion related artifacts, many studies simply remove the period of EEG data during motion via visual inspection [23], [24].…”
Section: B Motion Related Artifactsmentioning
confidence: 99%
“…Clearly, the use of EEG in driving research has multiple benefits over fMRI, particularly regarding its amenability to more naturalistic environments and tasks. However, similar to fMRI, EEG often suffers from methodological drawbacks, primarily related to motion artifacts 23 and environmental noise 24 , that hinder its use in studies of real-world driving. Moreover, the poor spatial resolution of EEG 25 often makes localization of cortical activity difficult, thus further reducing its ability to highlight specific cortical regions that underlie common driving behaviors.…”
Section: Introductionmentioning
confidence: 99%